DEVELOPMENT METHOD FOR THE DETERMINATION OF Cr, Cd AND Pb IN EDIBLE SUNFLOWER OIL USING EMULSION EXTRACTION-FAAS - MOHAMMED, IBRAHIM ABDULAZEEZ; SALEEM, PARWEEN HASHIM (Journal of Duhok University, 2023)
The presence of heavy metals in vegetable oils has negative health effects when consumed by living organisms. As a result, assessing mineral extraction methods is critical for monitoring mineral concentration levels and ensuring oil quality. This study describes a new analytical method for the determination of cadmium (Cd), chromium (Cr), and lead (Pb) in edible sunflower oil using emulsion extraction followed by flame atomic absorption spectroscopy (FAAS). The method is based on the formation of a water-in-oil emulsion by mixing the oil sample with (1, 10-2 and 10-3 M nitric acid solution for Pb, Cr, and Cd respectively) incorporated with a certain amount of a surfactant Triton-X 100 for Pb and Cr, and Tween 80 for Cd. Once the emulsion was formed, it was broken by centrifuging the mixture at 4000 rpm for 5 minutes. This led to the extraction of metal ions into the aqueous phase which was collected, and introduced to FAAS for metal analysis. Neither an organic solvent was used nor an additional dilution was performed prior to the metal analysis. Various parameters that may affect the extraction efficiency of the target metals were evaluated and optimized. The detection limits were 20.0 μg/kg for lead, 4.0 μg/kg for chromium, and 0.2 μg/kg for cadmium. The standard addition method was used for the construction of the calibration curve to mitigate the potential interferences caused by the sample matrix. The findings confirmed that the proposed sample preparation method combined with FAAS provides a simple and reliable analytical method for the measurement of lead, chromium, and cadmium in edible oils